2012
DOI: 10.1063/1.3693264
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on absorption, emission, and resonance Raman spectra of Coumarin 343 isomers

Abstract: The vibrationally resolved spectral method and quantum chemical calculations are employed to reveal the structural and spectral properties of Coumarin 343 (C343), an ideal candidate for organic dye photosensitizers, in vacuum and solution. The results manifest that the ground-state energies are dominantly determined by different placements of hydrogen atom in carboxylic group of C343 conformations. Compared to those in vacuum, the electronic absorption spectra in methanol solvent show a hyperchromic property t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 68 publications
3
19
0
Order By: Relevance
“…It has been demonstrated that the theoretically optimized molecular structures based on DFT calculations bear good agreement with the experimental derived data using X-ray diffraction. 47,48 TD-DFT has also been shown to be a powerful tool to model the spectroscopic properties of organic fluorophores. 49,50 In addition, empirical HOSE and BLA models, which successfully correlate the structural features of coumarins to their optoelectronic properties, 47,51 are applied in this study as well.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that the theoretically optimized molecular structures based on DFT calculations bear good agreement with the experimental derived data using X-ray diffraction. 47,48 TD-DFT has also been shown to be a powerful tool to model the spectroscopic properties of organic fluorophores. 49,50 In addition, empirical HOSE and BLA models, which successfully correlate the structural features of coumarins to their optoelectronic properties, 47,51 are applied in this study as well.…”
Section: Resultsmentioning
confidence: 99%
“…We have investigated several C343 isomers 37 , some of which are denoted as Ca, Cb and Cc as shown in Fig. However, it is a challenge to theoretically construct the suitable interface arrangement because of too many possibilities.…”
Section: Geometries and Electronic Structures Of C343-tiomentioning
confidence: 99%
“…However, it is a challenge to theoretically construct the suitable interface arrangement because of too many possibilities. It displays that the relative groundstate energies of different isomers are nearly independent of the N-ring conformers (anti-and syn-), and they are basically determined by the -COOH conformers 37 . We have investigated several C343 isomers 37 , some of which are denoted as Ca, Cb and Cc as shown in Fig.…”
Section: Geometries and Electronic Structures Of C343-tiomentioning
confidence: 99%
“…3 shows Raman spectra of current compound. From this plot, weak and strong peaks corresponding to given structure can be observed [19]. For example, C O (in pyrone ring) stretching high-frequency vibrations occur at 1446 cm −1 , 1546 cm −1 , and 1603 cm −1 respectively.…”
Section: Photoluminescence Studymentioning
confidence: 91%
“…The intensity of mode with CH 2 wagging and ring skeleton vibration motions (1298 cm −1 ) is relatively weak, but 1302 cm −1 and 1336 cm −1 are strong. The mode with 907 cm −1 corresponds to the out of plane bending of OH whereas the modes with 771 cm −1 are O C C COOH out of plane bending vibration [19]. Fig.…”
Section: Photoluminescence Studymentioning
confidence: 98%